Construction and validation of a method for automated time label segmentation of heart sounds - Li, Liuying; Huang, Min; Dao, Ling; Feng, Xixi; Liu, Yifeng; Wei, Changyou; Liu, Fangfang; Zhang, Jing; Xu, Fan (Frontiers in Artificial Intelligence, 2024)
Heart sound detection technology plays an important role in the prediction of cardiovascular disease, but the most significant heart sounds are fleeting and may be imperceptible. Hence, obtaining heart sound information in an efficient and accurate manner will be helpful for the prediction and diagnosis of heart disease. To obtain heart sound information, we designed an audio data analysis tool to segment the heart sounds from single heart cycle, and validated the heart rate using a finger oxygen meter. The results from our validated technique could be used to realise heart sound segmentation.Our robust algorithmic platform was able to segment the heart sounds, which could then be compared in terms of their difference from the background. A combination of an electronic stethoscope and artificial intelligence technology was used for the digital collection of heart sounds and the intelligent identification of the first (S1) and second (S2) heart sounds. Our approach can provide an objective basis for the auscultation of heart sounds and visual display of heart sounds and murmurs.